Assessing Factors That Constitute Talent in the Islamic Financial Institutions among Bank Officers - Zainol, Zairani; Daud, Zulkiflee (World Academy of Science, Engineering and Technology, 2016)
This study employed 86 respondents representing bank officers of Bank XYX (one of the full-fledged Islamic banks in Malaysia) in the northern region of Malaysia to assess the factors that constitute talent in the Islamic financial industries.To test the discriminant factors for talent among bank officers, a factor analysis was performed.The KMO, Bartlett and MSA tests were executed as the prerequisite before performing the factor analysis.The discriminant factors for talent were extracted via eigenvalues and rotated component matrixes.The results show that five factors, namely (1) self-motivation, (2) leadership, (3) teamwork, (4) interpersonal skills, and (5) creativity/innovation constitute talent in the Islamic financial industries.It is hoped that this study could offer guidelines to education providers, specifically those that conduct the Islamic finance and banking program, as to the areas of emphasis for students before graduating. For the Islamic financial institutions, this study is also vital since they could tackle the areas that need to be improved in managing their talents.